Gaucher disease – a comprehensive review of clinical characteristics, diagnostic algorythms and current therapies - Kotula, Alicja; Kucy, Natalia; Czachor, Adrianna; Kula, Paula; Haber, Mateusz; Grelewicz, Olga; Servaas, Elwira; Juśkiewicz, Adam; Pilcicka, Alicja (Quality in Sport, 2024)
Gaucher disease (GD) is an autosomal recessive lysosomal storage disorder caused by mutations in the GBA1 gene, which encodes the enzyme glucocerebrosidase. This enzyme is crucial for breaking down glucocerebrosides, and its deficiency leads to their accumulation in the monocyte-macrophage system, forming Gaucher cells. These cells build up in the bone marrow, spleen, and liver, causing various clinical manifestations. GD is classified into three types based on clinical features and progression: GD1 (non-neuronopathic), GD2 (acute neuronopathic), and GD3 (subacute neuronopathic). GD1, the most common form, usually presents with splenomegaly, hepatomegaly, anemia, thrombocytopenia, and skeletal symptoms and has a relatively mild course. GD2 is marked by severe neurological involvement, with a poor prognosis and a maximum survival of three years. GD3 features a mix of visceral, hematological, neurological, and skeletal symptoms, with a variable prognosis depending on the subtype. Epidemiologically, GD is rare in the general population but more common among Ashkenazi Jews, who have a higher carrier frequency and prevalence. The genetic basis of GD is well-documented, with several mutations associated with different disease severities and outcomes. Diagnostic procedures include a comprehensive medical history, imaging studies, and biochemical and genetic tests to confirm reduced glucocerebrosidase activity and identify GBA1 mutations. Current treatments focus on enzyme replacement therapy (ERT) and substrate reduction therapy (SRT), with supportive care for specific symptoms. ERT is the primary treatment for all children with GD1 and GD3 and for adults who meet certain criteria, while SRT is an alternative for milder forms of GD1. Despite advances in treatment, managing GD remains complex, requiring a multidisciplinary approach to address the diverse clinical manifestations and improve patient outcomes.